2011
DOI: 10.1002/humu.21534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical heterogeneity associated with fumarase deficiency

Abstract: Fumarase deficiency (FD), caused by biallelic alteration of the Fumarase Hydratase gene (FH), and a rare metabolic disorder that affects the Krebs cycle, causes severe neurological impairment and fumaric aciduria. Less than 30 unrelated cases are known to date. In addition, heterozygous mutations of the FH gene are responsible for hereditary leiomyomatosis and renal cell cancer (HLRCC). We report three additional patients with dramatically different clinical presentations of FD and novel missense mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
(52 reference statements)
4
36
0
Order By: Relevance
“…Therefore, dysfunctions in the mitochondrial TCA cycle may produce changes in oxidative energy production, contributing to skeletal muscle manifestations. Patients with FHD showing FH activity in skeletal muscle below 10% may develop muscular hypotonia . In this study, our patients showed low levels of FH activity in skeletal muscle that could explain the presence of myopathy.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Therefore, dysfunctions in the mitochondrial TCA cycle may produce changes in oxidative energy production, contributing to skeletal muscle manifestations. Patients with FHD showing FH activity in skeletal muscle below 10% may develop muscular hypotonia . In this study, our patients showed low levels of FH activity in skeletal muscle that could explain the presence of myopathy.…”
supporting
confidence: 46%
“…D ear E ditor , Fumarate hydratase (FH) catalyses the conversion of fumarate to malate as part of the tricarboxylic acid (TCA) cycle . Germline mutations in the FH gene may lead to autosomal recessive mutations causing FH deficiency (FHD), associated with neurological impairment in childhood and muscular hypotonia . Patients with heterozygous mutations may develop multiple cutaneous leiomyomas (CLs) and uterine leiomyomas (ULs), and they more frequently have type II papillary renal cell cancer (RCC) [hereditary leiomyomatosis and RCC (HLRCC)] .…”
mentioning
confidence: 99%
“…While α-ketoglutarate is necessary for the reaction to occur, succinate, fumarate and oxaloacetate inhibit the prolyl hydroxylases, leading to pseudo-hypoxia in tumor and embryonic cells [31, 32, 34-37] but not in non-transformed cells [30, 36, 38]. Pyruvate, citrate, isocitrate, fumarate and succinate inhibit PHDs in tumor cells, with fumarate showing the strongest effect [36, 39-41].…”
Section: The Tca Cycle In Control Of the Hypoxia Responsementioning
confidence: 99%
“…Silencing of FH in cultured tumor cells also lead to increased glycolytic metabolism and accumulation of HIF α-subunits [35]. However, no accumulation of HIF-1α was detected in primary fibroblasts with recessive FH defects and fumarate accumulation [30, 38]. It seems thus that intracellular fumarate accumulation triggers the pseudo-hypoxia response in tumor or embryonic cells, but not in primary fibroblasts.…”
Section: Mechanisms Beyond Hypoxiamentioning
confidence: 99%
“…5962 These patients usually do not survive beyond the first few months of life, although some more mildly affected individuals have been described. 63,64 Relatives with only one mutation, can go on to develop papillary type 2 renal cancer. Mutations have not been observed in sporadic RCC, but in part the lack of observation may arise due to the limited number of papillary type 2 tumors included in the screening series.…”
Section: Hereditary Papillary Renal Cancermentioning
confidence: 99%